PENGARUH KEMUDAHAN AKSES E-SAMSAT, KEPERCAYAAN TERHADAP PEMERINTAH, DAN BIAYA PAJAK TERHADAP MINAT MASYARAKAT MEMBAYAR PAJAK KENDARAAN BERMOTOR TEPAT WAKTU DI KOTA SURAKARTA - Anggun Cantika Dewi; Sri Isfantin Puji Lestari; Retnoning Ambarwati (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the effect of e-Samsat accessibility, trust in government, and tax costs on public interest in paying motor vehicle taxes on time in Surakarta City. Motor vehicle tax is an important source of regional revenue that supports regional development; however, delays in tax payments remain a significant issue. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 motor vehicle owners in Surakarta City selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that e-Samsat accessibility, trust in government, and tax costs have a positive and significant effect on public interest in paying motor vehicle taxes on time, both partially and simultaneously. Among the independent variables, tax cost was found to be the most dominant factor influencing taxpayers’ interest. These findings suggest that improving digital tax services, strengthening public trust in government, and implementing appropriate tax policies can enhance taxpayers’ willingness to fulfill their tax obligations on time. Keywords: e-Samsat, trust in government, tax cost, taxpayer interest, motor vehicle tax